British Indian picture postcards in Bengaluru - Stevenson, Emily (Emily Rose), author.
1 online resource (xii, 164 pages)
Keywords: "Combining ethnographic and archival research, this book examines the lives of colonial-period postcards and reveals how they become objects of contemporary historical imagination in India. Picture postcards were circulated around the world in their billions in the early twentieth century and remained, until the advent of social media, unmatched as the primary means of sharing images alongside personal messages. This book, based on original research in Bengaluru, shows that their lives stretch from their initial production and consumption in the early 1900s into the present where they act as visual and material mediators in postcolonial productions of history, locality and heritage against a backdrop of intense urban change. The book will be of interest to photographic historians, visual anthropologists, and art historians"--